1961
DOI: 10.1063/1.1732223
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacities and the Residual Entropy of Ta2H

Abstract: Heat capacities of Ta2H have been determined over a range of temperature extending from 12° to 555°K. Three very sharp A points were observed, at 306, 332, and 333.5°K, suggesting that Ta 2 H exists in four formS-#1 below 306°K, #2 between 306 and 332, #3 at about 333, and a above about 334°K. The heat capacity data for Ta2H are used together with similar data obtained earlier for elemental tantalum and the entropy of formation of Ta2H, evaluated from vapor pressure work by Kofstad, Wallace, and Hyviinen, to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…6 together with the previous results of Ta2H (5) and of the Ta-D alloys (9). The present data agree very well with the results of the Ta-D alloys, indicating the two systems isomorphic.…”
Section: Transformation Entropysupporting
confidence: 87%
“…6 together with the previous results of Ta2H (5) and of the Ta-D alloys (9). The present data agree very well with the results of the Ta-D alloys, indicating the two systems isomorphic.…”
Section: Transformation Entropysupporting
confidence: 87%
“…At temperatures around room temperature, at least two orthorhombic phases exist: an orthorhombic phase were the hydrogen atoms are partially ordered and one orthorhombic phase, close to stochiometric TaH 0.5 , in which the hydrogen atoms are fully ordered. All these phases are separated by two-phase regions, indicating first-order transitions with associated hysteresis, as confirmed by heat capacity and electrical resistivity measurements. ,, These first-order phase transitions are at variance with the observed hysteresis-free sensing range of thin film tantalum at room temperature. As such, it could imply either that the critical temperature is reduced in thin film tantalum and a solid solution of hydrogen and tantalum is formed at room temperature or that the nature of the transition changed from first to second order, thereby eliminating the hysteresis.…”
mentioning
confidence: 99%
“…Specific heat measurements as a function of temperature by Saba et al 302 showed two specific heat anomalies for TaH 0 . 5 in addition to the beta-to-alpha transformation at 61°C shown in Fig.…”
Section: Alpha-alpha Plus Betamentioning
confidence: 99%
“…Heat capacities of the Group V hydrides have been measured as a function of temperature by Bieganski and Stalinski 312d,317a and Saba et al 302 The curves for vanadium and niobium hydrides show no anomalies, but those of tantalum hydride exhibit the anomalies corresponding to the betai-to-beta 2 and beta 2 -to-beta 3 transitions discussed in Sec. 12-5.2(a)(3) and 12-5.3(c).…”
Section: (C) Thermal Propertiesmentioning
confidence: 99%